2016
DOI: 10.1097/wnp.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Intraoperative Neurophysiological Monitoring During Spine Surgery

Abstract: Intraoperative neurophysiologic monitoring has had major advances in the past few decades. During spine surgery, the use of multimodality monitoring enables us to assess the integrity of the spinal cord, nerve roots, and peripheral nerves. The authors present a practical approach to the current modalities in use during spine surgery, including somatosensory evoked potentials, motor evoked potentials, spinal D-waves, and free-run and triggered electromyography. Understanding the complementary nature of these mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, discharges can be seen with nerve stretch, blunt trauma, compression, or ischemia. High‐frequency or high‐amplitude responses suggest irritation to the nerve roots . After placing the needles or surface electrodes, the surgeon or his or her assistant performs a train‐of‐four twitch test to confirm that there are no long‐acting paralytics in the patient's circulatory system .…”
Section: Neuromonitoring and Anesthesiamentioning
confidence: 99%
“…However, discharges can be seen with nerve stretch, blunt trauma, compression, or ischemia. High‐frequency or high‐amplitude responses suggest irritation to the nerve roots . After placing the needles or surface electrodes, the surgeon or his or her assistant performs a train‐of‐four twitch test to confirm that there are no long‐acting paralytics in the patient's circulatory system .…”
Section: Neuromonitoring and Anesthesiamentioning
confidence: 99%
“…Various neurophysiologic monitoring modalities have been utilized to monitor the spinal cord intraoperatively during corrective scoliosis surgery, including motor evoked potentials (MEP) and somatosensory evoked potentials (SSEP). 3,4 Intraoperative monitoring and detection of alternations of the evoked potentials alerts the surgeon to possible neurological damage and the need for a corrective response to potentially reduce the risk of harm.…”
Section: Introductionmentioning
confidence: 99%
“…Raynor et al also attributed recordings' changes to systemic factors. Interestingly, IONM changes were more common in revision surgeries than in primary [1,40,[68][69][70][71].…”
Section: Spinal Cord Surgerymentioning
confidence: 99%
“…Nevertheless, preoperative motor weakness or neuromuscular scoliosis decrease MEP recording value, still, Wang et al concluded MEP monitoring is feasible for most high risk diagnosis and complicated surgical procedures with sudden loss meaning postoperative neurological deficit. Nevertheless, patients with preoperative deficit may present neuromonitoring signal drop with normal spinal function, so that, stays as an important question if monitoring loss is a strong predictor of PND [14,21,23,50,68,71,72].…”
Section: Spinal Cord Surgerymentioning
confidence: 99%